1989
DOI: 10.1063/1.342554
|View full text |Cite
|
Sign up to set email alerts
|

Coupled GaAs/AlGaAs quantum-well electroabsorption modulators for low-electric-field optical modulation

Abstract: Experimental and theoretical studies are presented for exciton transitions in p-i-n GaAs/AlGaAs multiple coupled-quantum-well structures where each quantum well consists of two identical wells with a thin barrier. Electroabsorption and photocurrent studies are carried out to identify how the excitonic peaks respond to transverse electric fields. With a careful choice of the dimensions of the coupled quantum well, it is seen that the lowest heavy-hole exciton peak moves at a rate ∼2.5 faster than in a square we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…On the other hand, in coupled quantum wells and superlattices the wave functions can become strongly distorted with increasing applied field, leading to stronger electric field dependence of subband energies and oscillator strengths. 14,15 Furthermore, introducing an asymmetry between the two wells of the structure enhances the separation of the electron and hole wave functions down to zero field, leading to a linear ͑Pockels͒ electro-optic effect that can exceed quadratic contributions at sufficiently low fields.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in coupled quantum wells and superlattices the wave functions can become strongly distorted with increasing applied field, leading to stronger electric field dependence of subband energies and oscillator strengths. 14,15 Furthermore, introducing an asymmetry between the two wells of the structure enhances the separation of the electron and hole wave functions down to zero field, leading to a linear ͑Pockels͒ electro-optic effect that can exceed quadratic contributions at sufficiently low fields.…”
Section: Introductionmentioning
confidence: 99%
“…The absorber MQW placement in the top DBR coincides with an antinode of the optical standing wave, thereby maximizing efficiency of the absorption process. We chose to use a coupled-QW architecture to maximize the electric field dependence of exciton absorption wavelength [8]. The distance from the active region is determined so that maximum absorption will not shut off the laser, and maximum modulation depth is obtained.…”
Section: Device Descriptionmentioning
confidence: 99%
“…Even though some studies of interwell coupling in coupled systems have been reported, most of them have been done on double QW structures without involving DMS's ͑i.e., without the advantage of continuous tuning͒; [20][21][22][23][24][25] and, more importantly, these studies focused primarily on the dependence of coupling strength on the properties of the separating barriers ͑i.e., on their width and height͒. 26,27 It is obvious that the strength of the coupling between the wells is determined not only by the barrier properties, but also by the relative alignment of the wells themselves ͑i.e., whether or not the system is in a resonant con-dition͒.…”
Section: Introductionmentioning
confidence: 99%